CHARACTER EDUCATION IN THE ACEHNESE IDIOMS OF KUALA BATEE COMMUNITY OF SOUTHWEST ACEH - Sanusi Sanusi (Jurnal Ilmiah Didaktika, 2021)
This study is entitled "Character Education in the Acehnese Idiom in the Kuala Batee Community of Southwest Aceh”. The Acehnese idiom was used as a support in advising and as a means of maintaining existing norms in the society. A Society is one of the most influential molders of character education because of its interactions. The values of traditional culture are recognized by all levels of the society in the regions and nationalities that become national identities. Not only culture, local languages also need to be used in daily interactions in society so that they do not experience a serious decline, which will eventually disappear over the time. In this case, the Acehnese Idiom became a medium to spread the value of character education to the next generation. The purpose of this study is to describe the Acehnese expressions that contain the values of character education in the community of Kuala Batee Southwest Aceh. The method of this research is a descriptive qualitative. Interview was used as an instrument. In this study, 8 subjects are chosen using purposive sampling that consist of tuhapheut and village elders in the community. The location of this study is in Kuala Batee District, Southwest Aceh.  There are 18 character values in the Acehnese Idiom in the community of Kuala Batee, Southwest Aceh which consists of; religious, honest, tolerance, discipline, hard work, creative, independent, democratic, curiosity, national spirit, love of the homeland, respect for achievement, friendly/communicative, love peace, love to read, care for the environment, social care and responsibility. The expressions found in the Kuala Batee community are in the form of one line, two lines, three lines and four lines. The Acehnese idiom in the community of Kuala Batee Southwest Aceh is in the oral form which has its own meaning and use as an advice relating to divinity, self, others and the environment. Based on the above conclusions, the author suggests the community to preserve the Acehnese idiom so that it becomes a legacy for the next generation. To the government, it is hoped that they will support to publish references related to Acehnese idioms and other types of folklore related to Acehnese culture so that they can add references to other studies.